Local adaptation to the native environment affects pyrethrin variability in Dalmatian pyrethrum populations - Grdiša, Martina; Jeran, Nina; Varga, Filip; Liber, Zlatko; Turudić, Ante; Šatović, Zlatko (Frontiers in Plant Science, 2024)
The insecticidal compound pyrethrin is synthesized in Dalmatian pyrethrum (Tanacetum cinerariifolium (Trevis.) Sch.Bip.; Asteraceae), a plant species endemic to the eastern Mediterranean. Pyrethrin is a mixture of six compounds, pyrethrin I and II, cinerin I and II, and jasmolin I and II. For this study we sampled 15 natural Dalmatian pyrethrum populations covering the entire natural distribution range of the species; Croatian coastal regions and the islands, inland Bosnia and Herzegovina and Montenegro. The plants were grown in a field experiment under uniform growing conditions to exclude a short-term response to environmental factors and instead observe variation in pyrethrin content and composition among and within populations due to genetic adaptation to the native environment. The drivers of local adaptation were explored by examining the role of bioclimatic factors as a cause of population differentiation. Pyrethrins were extracted by ultrasound-assisted extraction, and the extracts were analyzed by HPLC-UV-DAD. The populations differed significantly in the content and composition of pyrethrins. The highest levels of total pyrethrins (1.27% flower DW), were found in population P14 Budva and the significantly highest levels of pyrethrin I in population P14 Vranjske Njive, Podgorica (66.47% of total pyrethrin). Based on bioclimatic conditions of the sampling sites, populations were grouped into five bioclimatic groups (A, B, C, D, and E), which showed qualitative and quantitative variability in pyrethrin content. The most abundant bioclimatic group was bioclimatic group E, which was characterized by the highest average values for pyrethrin I (53.87% of total pyrethrin), total pyrethrin content (1.06% flower DW) and the ratio of pyrethrin I and II (1.85). The correlation analysis between the pyrethrin compounds and some of the bioclimatic variables (e. g., BIO03 Isothermality and BIO04 Temperature seasonality) showed their significant contribution in explaining the variation of pyrethrins in T. cinerariifolium. The differences in pyrethrin content and composition may be partly due to genetic adaptation to the ecological conditions of the native environment. The obtained data would enable the selection of source populations for breeding programs aimed at producing cultivars with desirable biochemical properties and adaptation to different bioclimatic conditions.